2021
DOI: 10.47363/jalp/2021(2)109
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Nutritional Strategies to Reduce Methane Emission from Large Ruminants: Review

Abstract: Livestock are considered as a main source of GHGs emission by contributing approximately 9% of the total global emission and a major concern for global warming. Domestic animals account approximately 94% of the total global emissions of animals from these large ruminants (dairy and beef cattle) produce 30% and 35% of the livestock sectors’ emissions. Most methane (CH4) that is emitted from livestock originates in the forestomach, also called the rumen, of ruminants. Minimizing amount of methane that comes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Conversely, "Other Bovines" was the most efficient category, emitting a lower amount of CH 4 of enteric origin. Higher-quality feed that is less susceptible to variations during the year is more efficient, resulting in lower amounts of CH 4 being produced [31]. Our findings revealed that in the Azores, the average methane emissions per head per year for each bovine are about 68.8 kg CH 4 .…”
Section: Discussionmentioning
confidence: 71%
“…Conversely, "Other Bovines" was the most efficient category, emitting a lower amount of CH 4 of enteric origin. Higher-quality feed that is less susceptible to variations during the year is more efficient, resulting in lower amounts of CH 4 being produced [31]. Our findings revealed that in the Azores, the average methane emissions per head per year for each bovine are about 68.8 kg CH 4 .…”
Section: Discussionmentioning
confidence: 71%